2014
DOI: 10.2217/nnm.12.217
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cytotoxicity and Particle Action of Hydroxyapatite Nanoparticles in Human Cancer Cells

Abstract: Varying cytotoxicity of HAPNs was observed in different cancer cell types. Our results suggest that possible mechanisms of cytotoxicity in various types of cancer cells could be different. The elevated calcium concentration and nuclear localization of the particles might be the main mechanism of growth inhibition by HAPNs in cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 37 publications
5
60
1
Order By: Relevance
“…E.g., a recent study on the impact of amorphous SNPs in three pairs of murine/human cell lines (lung epithelium, macrophages, and colon epithelium) found that macrophages were the most sensitive cell type among the three pairs, whereas murine cell lines were more sensitive than comparable human cell lines . Another study revealed that HUVECs were more sensitive than HeLa cells upon 310 nm SNPs exposure, and we also demonstrated differential toxicity of hydroxyapatite nanoparticles in human cancer cells with an order of MGC80–3 > HepG2 > HeLa . These results clearly show that cytotoxic effects of nanoparticles cannot be generalized and transferred from one cell type to another.…”
Section: Discussionsupporting
confidence: 68%
“…E.g., a recent study on the impact of amorphous SNPs in three pairs of murine/human cell lines (lung epithelium, macrophages, and colon epithelium) found that macrophages were the most sensitive cell type among the three pairs, whereas murine cell lines were more sensitive than comparable human cell lines . Another study revealed that HUVECs were more sensitive than HeLa cells upon 310 nm SNPs exposure, and we also demonstrated differential toxicity of hydroxyapatite nanoparticles in human cancer cells with an order of MGC80–3 > HepG2 > HeLa . These results clearly show that cytotoxic effects of nanoparticles cannot be generalized and transferred from one cell type to another.…”
Section: Discussionsupporting
confidence: 68%
“…The analysis of reactive oxide species in the conditioned media revealed no statistically significant differences between the analysed groups. It is known that hydroxyapatite may induce the formation of reactive oxygen species, however, its cytotoxicity may differ between different cell types, as shown previously [28]. The supernatants of cells cultured on biomaterial 4, 6 and 8 under chondrogenic and osteogenic conditions had lower concentrations of nitric oxide than the respective non-stimulated control groups.…”
Section: Quantitative Analysis Of Cellular Oxidative Stress Factorssupporting
confidence: 54%
“…The cytotoxic effect of np20 and np80 on HUVECs could be attributed to the induction of oxidative stress by HANPs as well as elevated intracellular calcium concentration due to substantial uptake of HANPs (Figures 3-5). 30,31 To date, the cytotoxicity of HANPs still remains a matter of debate. It has also been reported that HANPs were compatible to mouse bone marrow mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%